Characterizing languages of polymorphic P systems by parallel communicating Lindenmayer systems - Kuczik, Anna; Vaszil, György (Natural computing, 2025)
We continue the investigation of the computational power of non-cooperative polymorphic P systems with no ingredients (no target indicators or any special features added to the rules) in terms of parallel communicating Lindenmayer systems. We precisely characterize the language class generated by these types of P systems using a restricted class of parallel communicating ET0L systems. Our results demonstrate that the dynamically changing rewriting rules provided by the polymorphic framework in non-cooperating P systems results in a similar increase in computational power as a restricted variant of the parallel communicating framework does in the power of ET0L systems.